Layer‐By‐Layer Printing Strategy for High‐Performance Flexible Electronic Devices with Low‐Temperature Catalyzed Solution‐Processed SiO2. Issue 8 (21st May 2021) - Sun, Qingqing; Gao, Tianqi; Li, Xiaomeng; Li, Wanli; Li, Xiaoqian; Sakamoto, Kenji; Wang, Yong; Li, Lingying; Kanehara, Masayuki; Liu, Chuan; Pang, Xinchang; Liu, Xuying; et al.
Abstract: Additive printing techniques have been widely investigated for fabricating multilayered electronic devices. In this work, a layer‐by‐layer printing strategy is developed to fabricate multilayered electronics including 3D conductive circuits and thin‐film transistors (TFTs) with low‐temperature catalyzed, solution‐processed SiO2 (LCSS) as the dielectric. Ultrafine, ultrasmooth LCSS films can be facilely formed at 90 °C on a wide variety of organic and inorganic substrates, offering a versatile platform to construct complex heterojunction structures with layer‐by‐layer fashion at microscale. The high‐resolution 3D conductive circuits formed with gold nanoparticles inside the LCSS dielectric demonstrate a high‐speed response to the transient voltage in less than 1 µs. The TFTs with semiconducting single‐wall carbon nanotubes can be operated with the accumulation mode at a low voltage of 1 V and exhibit average field‐effect mobility of 70 cm 2 V −1 s −1, on/off ratio of 10 7, small average hysteresis of 0.1 V, and high yield up to 100% as well as long‐term stability, high negative‐gate bias stability, and good mechanical stability. Therefore, the layer‐by‐layer printing strategy with the LCSS film is promising to assemble large‐scale, high‐resolution, and high‐performance flexible electronics and to provide a fundamental understanding for correlating dielectric properties with device performance. Abstract : A layer‐by‐layer printing strategy is developed to fabricate flexible 3D conductive circuits and thin‐film transistors (TFTs) with low‐temperature catalyzed, solution‐processed SiO2 as the dielectric. The high‐resolution 3D conductive circuits demonstrate a high‐speed response to the transient voltage less than 1 µs. The semiconducting‐single‐carbon‐nanotube TFTs can be operated at low voltages of 1 V with high electrical and mechanical stability.